ANALISIS FUNGSI KEUNTUNGAN PADA USAHATANI KEDELAI DI LAHAN SAWAH DAN DARAT - Rian Kurnia; Ivan Sayid Nurahman; Saepul Aziz (Universitas Galuh Ciamis, 2020)
This study aims to analyze the effect of the use of production factors on profits in soybean farming in paddy fields and dry land in Jatiwaras District, Tasikmalaya Regency. The sample was determined using Multistage Cluster Random Sampling, so that a sample size of 127 people from a population of 185 people consisted of 52 farmers in the paddy fields and 75 farmers in the dry land. The results showed simultaneously the price of seeds, the price of fertilizer, the price of pesticides, labor costs, land area and the depreciation of the equipment have a very significant effect on profits. In model II it can be seen that the estimator of the profit function has an R2 of 0.4960. In model II it appears that the price of seeds, the price of fertilizer, and land area, has a negative relationship with profits; while the price of pesticides, labor costs, land area, and equipment depreciation have a positive relationship with profits. Partially the area of land has a significant effect on profits.